2017
DOI: 10.1158/1078-0432.ccr-16-1591
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-221 Enhances MYCN via Targeting Nemo-like Kinase and Functions as an Oncogene Related to Poor Prognosis in Neuroblastoma

Abstract: Purpose: MYCN is one of the most well-characterized genetic markers of neuroblastoma. However, the mechanisms as to how MYCN mediate neuroblastoma tumorigenesis are not fully clear. Increasing evidence has confirmed that the dysregulation of miRNAs is involved in MYCN-mediated neuroblastoma tumorigenesis, supporting their potential as therapeutic targets for neuroblastoma. Although miR-221 has been reported as one of the upregulated miRNAs, the interplay between miR-221 and MYCN-mediated neuroblastoma progress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…From these observations we anticipated that miRNAs could act as a proxy to capture stem cell features in neuroblastoma cells. Indeed, it has already been shown that miRNAs play important roles in neuroblastoma tumor formation and progression 15 , 16 . The let-7 cluster, previously described as crucial to be downregulated for maintaining pluripotency in stem cells 17 , is frequently lost in neuroblastoma, inversely associated with MYCN amplification status and independently correlated with poor prognosis 18 .…”
Section: Introductionmentioning
confidence: 99%
“…From these observations we anticipated that miRNAs could act as a proxy to capture stem cell features in neuroblastoma cells. Indeed, it has already been shown that miRNAs play important roles in neuroblastoma tumor formation and progression 15 , 16 . The let-7 cluster, previously described as crucial to be downregulated for maintaining pluripotency in stem cells 17 , is frequently lost in neuroblastoma, inversely associated with MYCN amplification status and independently correlated with poor prognosis 18 .…”
Section: Introductionmentioning
confidence: 99%
“… 24 Through enhancing MYCN, miR-221 is considered as an oncogene linked with unfavorable prognosis in neuroblastoma. 40 It has also been reported that highly MYCN expression in neural stem cells of the developing mouse could lead to the development of GBM. 41 Moreover, MYCN can be targeted and negatively regulated by miR-34a in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the function and effects of these miRNAs as stated in the literature might give some clues as to what the underlying mechanisms might be: for hsa-let-7f-5p, a proangiogenic effect has been reported; thus, overexpression might contribute to tumor progression via tumor neoangiogenesis [38][39][40]. For hsa-miRNA-221-3p, cell cycle regulation has been reported as a key mechanism in tumor progression; in addition, in cervical cancer, increased expression levels are associated with epithelialmesenchymal transition, migration, and invasion by targeting TWIST2 [41,42]. For human glioblastomas, cervical and colon carcinoma cells downregulation of PTEN and activation of Akt and STAT3-mediated by increased levels of hsa-miRNA-221-3p-have been shown as key players in tumor cell survival and radio-and chemoresistance [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%